Shariah and legal issues in house buying in Malaysia: the legality of Bay’Bithaman-al-Ajil (‘BBA’) with special reference to abandoned housing projects - Mohd. Dahlan, Nuarrual Hilal; Syed Abdul Kader, Sharifah Zubaidah (Universiti Putra Malaysia, 2011)
The primary duties of Islamic banks and financial institutions in Malaysia are to carry out Islamic banking and financial activities and to offer products that are in accordance with the Islamic teachings. These products are subject to the scrutiny and approval of Bank Negara’s Shariah Advisory Council (SAC) and the internal Shariah Advisory Bodies (SAB) or the Shariah Committees of the respective financial institutions. Despite having been in existence for more than 25 years, in the authors’ view, it is still questionable whether or not the Islamic banks and financial institutions in Malaysia have been satisfactorily carrying out these duties. One area worth examining is the transaction involving house buying, particularly the one that falls under the purview of the Housing Development (Control and Licensing) Act 1966 (Act 118) and transactions involving houses pending completion. This paper examines this area of transaction and the loan agreement, affected via Bay’ Bithaman al-Ajil (BBA), provided by Islamic banking and financial institutions in Malaysia. The purpose is to see to what extent the sale and purchase agreement and the loan agreement have complied with the requirements of the Islamic Law in protecting stakeholders and to provide practical suggestions to improve the existing practice. The paper concludes that the current practice of the BBA contradicts with the teachings of Islam and should therefore be modified and revamped until it is fully able to protect the interests of the purchasers/borrowers.